Perancangan Identitas Visual Kampanye Edukasi Pencegahan KDRT Untuk Perempuan Dewasa Awal - Putri, Yazmin Mahira; El Chidtian, Aileena Solicitor Costa Rica; Ayuswantana, Alfian Candra (Jurnal Ilmiah Wahana Pendidikan, 2024)
A campaign is a planned activity of conveying information with the aim of influencing a person's views and attitudes which is carried out in stages at a certain time. Life in the household cannot be separated from existing household problems. Problems in the household that are too severe lead to divorce. One of the factors in household problems that lead to divorce is domestic violence. Domestic violence cases are dominated by female victims according to the National Commission on Violence Against Women's Notes in 2023. The aim of designing the visual identity of the campaign logo is to provide awareness education to unmarried women about the importance of preventing domestic violence for their future married life. In this design, data collection methods using interviews, FGD and observation were used. This data was analyzed using fishbone analysis techniques to produce the keywords "Careful Education in Choosing a Life Partner" as a reference for verbal and visual concepts in designing the visual identity of the educational campaign logo. The results of the logo design are implemented on Instagram social media. It is hoped that this educational campaign can be a form of women's efforts to prevent domestic violence in the future..